High-performance plastic made from renewable oils is chemically recyclable by design - Williams, CK; Gregory, GL (Nature Research, 2021)
Plastics are invaluable materials, but they use up petroleum resources and persist in the environment. A high-performance plastic derived from renewable oils has been designed at the molecular level to be truly recyclable.